Impact of energy consumption on environment sustainability in upholding ESG practices in Malaysia: Evidence from electricity supply company. - Muhummad Khairul Islam; Muhammad Nazmul Hoque; Kazi Musa; Nisaa Husnina Binti Zulkifli (PLoS ONE)
This study aims to examine the impact of energy consumption, i.e., coal and gas, on environmental sustainability by utilizing CO2 emissions as a proxy to emphasize Environmental, Social, and Governance (ESG) practices in the electricity supply company of Malaysia. To do so, we collect time series data from Tenaga Nasional Berhad (TNB) Sustainability Reports spanning 2016-2021. Since the data is short time series data, this study deploys the Prais-Winsten (AR1) regression technique, which is able to produce robust estimates from the short data. Besides, this method is also able to overcome the issues of heteroscedasticity and autocorrelation issues in the dataset. Additionally, we also employ the Ordinary Least Square (OLS) regression method to check the robustness of our estimation. The findings of the study reveal that energy consumption, i.e., coal and gas, strongly affects the environmental sustainability channel through CO2 emissions. The result indicates that the electricity supply company of Malaysia still aggravates the environmental degradation using coal and gas in energy production, while the study also shows from the long-run trends that the sector has considerably decreased the CO2 emissions in recent years by 0.60%. Since the emission is still significant, this study emphasizes the need for a cautious approach to energy sources in order to reduce environmental effects. The study suggests that policymakers should review the existing energy use and CO2 emissions policy to strengthen environmental sustainability and ESG standards in Malaysia's electricity generation industry, reduce dependency on fossil fuels, and hasten the adoption of renewable energy sources.